2018
DOI: 10.1039/c8ra03619e
|View full text |Cite
|
Sign up to set email alerts
|

Modulating effect of selected pharmaceuticals on bone in female rats exposed to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)

Abstract: This paper discusses the problems regarding the influence of TCDD on the mechanical properties and structure of the bone tissue in female rats treated with the dioxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The previous reports confirm the need to search for substances that eliminate or reduce the effects of dioxins on the bone tissue [ 4 , 19 , 48 , 50 ].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The previous reports confirm the need to search for substances that eliminate or reduce the effects of dioxins on the bone tissue [ 4 , 19 , 48 , 50 ].…”
Section: Discussionmentioning
confidence: 53%
“…Previous experimental studies have proven the adverse effects of dioxins as environmental factors on bone remodeling in the experimental animals, both in developmental and adult age [ 43 ]. It was found that exposure to TCDD led to decrease of bone mechanical strength and caused an increase in density of cortical bone in studied adult rats [ 4 , 19 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…73 Moreover, abnormalities in bone mineralization and lower concentrations of calcium and magnesium as well as disorders of the teeth development were observed in newborns from mothers exposed to dioxins. 31,74 Dioxins pass to the fetus through the placenta resulting in disorders of organogenesis including skeletal system and stomatognathic apparatus. 75,76 As an example of the impact of dioxin accumulation on the development of cleft palate, two cases can be described briefly.…”
Section: Dioxin Accumulation and Its Impact On Orofacial Clefts Develmentioning
confidence: 99%